To solve the problem, we will first identify the vertex of the quadratic function \( f(x) = -(x + 1.4)^2 + 6 \) and then calculate the function values for the given \( x \) values.
Part A: Identify the vertex
The vertex form of a quadratic function \( f(x) = a(x - h)^2 + k \) gives the vertex as the point \( (h, k) \).
In the function given: \[ f(x) = -(x + 1.4)^2 + 6 \] we can see that:
- \( h = -1.4 \)
- \( k = 6 \)
Therefore, the vertex is: \[ \text{Vertex} = (-1.4, 6) \]
Part B: Complete the table
Now we will calculate \( f(x) \) for the given \( x \) values.
-
For \( x = 0 \): \[ f(0) = - (0 + 1.4)^2 + 6 = - (1.4)^2 + 6 = -1.96 + 6 = 4.04 \]
-
For \( x = 1 \): \[ f(1) = - (1 + 1.4)^2 + 6 = - (2.4)^2 + 6 = -5.76 + 6 = 0.24 \]
-
For \( x = 2 \): \[ f(2) = - (2 + 1.4)^2 + 6 = - (3.4)^2 + 6 = -11.56 + 6 = -5.56 \]
-
For \( x = 3 \): \[ f(3) = - (3 + 1.4)^2 + 6 = - (4.4)^2 + 6 = -19.36 + 6 = -13.36 \]
-
For \( x = 4.04 \): \[ f(4.04) = - (4.04 + 1.4)^2 + 6 = - (5.44)^2 + 6 = -29.5936 + 6 = -23.5936 \]
Now we can compile these results into the completed table:
| x | f(x) | |-------|----------| | 0 | 4.04 | | 4.04 | -23.5936 | | 1 | 0.24 | | 2 | -5.56 | | 3 | -13.36 |
Summary
- Vertex: \((-1.4, 6)\)
- Completed Table:
| x | f(x) | |-------|----------| | 0 | 4.04 | | 4.04 | -23.5936 | | 1 | 0.24 | | 2 | -5.56 | | 3 | -13.36 |